2005
DOI: 10.1111/j.1365-2958.2005.04521.x
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae secretes chromosomal DNA via a novel type IV secretion system

Abstract: SummaryThe process of DNA donation for natural transformation of bacteria is poorly understood and has been assumed to involve bacterial cell death. Recently in Neisseria gonorrhoeae we found that mutations in three genes in the gonococcal genetic island (GGI) reduced the ability of a strain to act as a donor in transformation and to release DNA into the culture. To better characterize the GGI and the process of DNA donation, the 57 kb genetic island was cloned, sequenced and subjected to insertional mutagenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
431
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 267 publications
(439 citation statements)
references
References 61 publications
6
431
1
1
Order By: Relevance
“…Species such as Neisseria are capable of active DNA export (Hamilton et al, 2005) and also DNA transport through vesiculation has been suggested (Whitchurch et al, 2002;Allesen-Holm et al, 2006). However, as opposed to active transport, several studies provide evidence that, in biofilms of many bacterial species, eDNA rather originates from the lysis of a cellular subpopulation.…”
Section: Mutants Lacking the Prophages Are Defective In Biofilm Formamentioning
confidence: 99%
“…Species such as Neisseria are capable of active DNA export (Hamilton et al, 2005) and also DNA transport through vesiculation has been suggested (Whitchurch et al, 2002;Allesen-Holm et al, 2006). However, as opposed to active transport, several studies provide evidence that, in biofilms of many bacterial species, eDNA rather originates from the lysis of a cellular subpopulation.…”
Section: Mutants Lacking the Prophages Are Defective In Biofilm Formamentioning
confidence: 99%
“…T4SSs are perhaps the most versatile of the macromolecular transport systems, being essential for host colonization by many medically important microbes [8][9][10][11][12][13] , the horizontal transfer of genetic material between bacteria and from bacteria to plants 2 as well as the special cases of the Helicobacter pylori DNA uptake 14 and Neisseria gonorrhoeae DNA release 15 systems. The prototypical T4SS is that of the plant pathogen Agrobacterium tumefaciens that uses its Vir system to cause tumours in most dicotyledonous species 16 .…”
mentioning
confidence: 99%
“…Neisseria species contain an unusually long IMEX called the gonococcal genomic island (GGI) (8). In Neisseria gonorrheae, the GGI is 57 kb long and encodes a type IV secretion system that exports the chromosomal DNA of its host, rendering it available to neighboring cells for gene exchange by genetic transformation (8,18). The GGI carries a dif site, dif GGI , consisting of a XerC-binding site, a central region homologous to the Neisseria dif site, dif Ng , and a divergent XerD-binding site (Fig.…”
mentioning
confidence: 99%